Prevalence of Child Maltreatment and the Effects of the Intergenerational Transmission of Violence on Attitudes towards Domestic Violence in Chinese Police Cadets - Hayes, Brittany E. (Journal of family violence, 2021)
In 2015, China passed legislation that criminalized domestic violence/child maltreatment and provided protections to victims of child maltreatment. Consistent with the intergenerational transmission of violence, prior cross-national research has demonstrated that the experience of child maltreatment is positively associated with supportive attitudes toward domestic violence. However, research conducted within China among Chinese police cadets has not found a relationship between child maltreatment and attitudes toward dating violence. The goals of the current study were to: 1) provide prevalence estimates of child maltreatment – including if the cadet witnessed domestic violence; 2) examine gender differences in the experience of child maltreatment and attitudes toward domestic violence, and; 3) examine if child maltreatment or witnessing domestic violence were associated with attitudes toward domestic violence. Survey data from 404 police cadets attending Zhejiang Police College in Hangzhou, China were analyzed. The majority of cadets (64.10%) experienced child maltreatment. Close to one in five cadets (19.10%) witnessed domestic violence in their household. Significant differences did not emerge between male and female cadets with regard to child maltreatment or witnessing domestic violence. Male cadets reported more supportive attitudes toward domestic violence than female cadets. Child maltreatment and witnessing domestic violence were not associated with attitudes toward domestic violence. Support was not found for the intergenerational transmission of violence among this sample of Chinese police cadets. Implications for future trainings and research are discussed.